The "action cam" phenomenon: a new trend in audiovisual production (Communication & Society, 2015)
When the GoPro camera was first put on the market in 2004, it brought about a new generation of ultracompact cameras designed to be attached to the user’s body, and which came to be known as action cams. Their principal characteristics were their tiny size, their high-quality images and a wide-angle, fixed-focal-length lens. This combination has made it much simpler to get spectacular subjective shots with considerable depth of field. The users of this technology now form a whole generation of citizen-filmmakers who produce thousands of videos every day in a novel realistic style dominated by first person narrative. Their work is principally shared via video platforms like YouTube and Vimeo, which provide instant feedback in the form of millions of views. In this paper we analize the common features of the action cam recording style and we state these videos will bring about a redefinition of the realist visual style. Furthermore, we propose to relate the success of the action cam phenomenon with the cognitive concept of embodiment and argue that the viewer’s mirror neurons copy the real sensations and enable the viewer to experience, virtually and in safety, the same emotions felt by the person actually taking part in the action..